2017
DOI: 10.1039/c7ew00087a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating bacterial community changes and organic substrate degradation in microbial fuel cells operating on real human urine

Abstract: New insights are reported on the degradation of organics in urine, changes in the anodic bacterial community and MFC performance on urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…In a BES, the current density depends on the oxidation of organic matter (COD) by microorganisms. The oxidation of organic matter by microorganisms, in turn, depends on the amount and nature of organic compounds, anode potential and other factors also affecting the microorganisms, such as pH . At the same time, the COD:TAN ratio of a certain wastewater is fixed, so manipulating the TAN loading rate also would affect the COD loading and therefore the current density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a BES, the current density depends on the oxidation of organic matter (COD) by microorganisms. The oxidation of organic matter by microorganisms, in turn, depends on the amount and nature of organic compounds, anode potential and other factors also affecting the microorganisms, such as pH . At the same time, the COD:TAN ratio of a certain wastewater is fixed, so manipulating the TAN loading rate also would affect the COD loading and therefore the current density.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of organic matter by microorganisms, in turn, depends on the amount and nature of organic compounds, anode potential and other factors also affecting the microorganisms, such as pH. [22][23][24] At the same time, the COD:TAN ratio of a certain wastewater is fixed, so manipulating the TAN loading rate also would affect the COD loading and therefore the current density. The load ratio, thus, might be a difficult parameter to control in a BES.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other studies have found no negative effects on the bioanode performance at neutral anolyte pH and concentrations of up to 5 g L -1 [194], at anolyte pH around 8 with a TAN concentration of 3.9 g L -1 [195] and even at anolyte pH of 8.85 and a TAN concentration of 4 g L -1 [69]. Several studies report that the inhibition effects can be overcome by acclimatizing the system to increasingly high TAN concentrations, and it has been found that higher current densities are reached in acclimatized BES compared to controls without acclimatization [171,196]. Other studies, however, report inhibition even after acclimatization periods [190,192].…”
Section: Probable Toxicity Of Urine To Microorganisms In Besmentioning
confidence: 99%
“…Stress due to high conductivity of the medium has also been suggested as a cause of inhibition at high TAN concentrations. This effect was studied on Corynebacterium glutamicum (which has been found in the microbial community of urine MFCs [171]), Escherichia coli, and Bacillus subtilis [198]. All three bacteria were resistant to ammonium up until a concentration of around 1 M (NH 4 ) 2 SO 4 (28 gTAN L -1 ), where growth inhibition was observed.…”
Section: Probable Toxicity Of Urine To Microorganisms In Besmentioning
confidence: 99%
See 1 more Smart Citation